2006
DOI: 10.1111/j.1365-4632.2006.02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination therapy with systemic glucantime and pentoxifylline in the treatment of cutaneous leishmaniasis

Abstract: The result obtained by two therapeutic methods indicates that combined therapy with Glucantime and pentoxifylline is more effective than Glucantime alone (P < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 10 publications
1
49
0
2
Order By: Relevance
“…Sadeghian and Nilforoushzadeh 41 reported that combined treatment with oral pentoxifylline (400 mg thrice daily) and a 2-week standard course of intramuscular MA injections was more effective than MA injections alone (P \ .05). Asilian et al, 46 in an RCT comprising a large sample, found carbon dioxide laser more effective than intramuscular injections of MA for 2 weeks (P \.05).…”
Section: Cryotherapy Alone or In Combination With Other Treatmentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sadeghian and Nilforoushzadeh 41 reported that combined treatment with oral pentoxifylline (400 mg thrice daily) and a 2-week standard course of intramuscular MA injections was more effective than MA injections alone (P \ .05). Asilian et al, 46 in an RCT comprising a large sample, found carbon dioxide laser more effective than intramuscular injections of MA for 2 weeks (P \.05).…”
Section: Cryotherapy Alone or In Combination With Other Treatmentsmentioning
confidence: 97%
“…7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Twenty-four RCTs are included in this group, two of which were also described in other groups. Predictably, this group was dramatically made up of heterogenic studies.…”
Section: Cryotherapy Alone or In Combination With Other Treatmentsmentioning
confidence: 99%
“…3,8 Pentoxifylline is a metilxantine used to treat vascular and chronic inflammatory diseases. 9,10 Pentoxifylline inhibits TNF-α production, 11 and the association of pentoxifylline plus antimony decreases the healing time of CL and ML, 12,13 is more effective than antimony alone, 10,11 and cures ML and CL patients refractory to Sb v therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In published RCTs, parenteral antimonials were equivalent or inferior to those administered intralesionally [22]. One small study suggests improved efficacy with adjunctive pentoxifylline (81.3 % n=26/32 vs. 50 % n=16/32) [49]. Despite poor evidence, experts endorse systemic antimonials in some national guidelines and continue to use them for complex, treatment refractory OWCL [47,98].…”
Section: Pentavalent Antimony (Sbv)mentioning
confidence: 96%